2020
DOI: 10.3390/w12123303
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Groundwater–Surface Water Interaction Applying the Hyporheic Flux Model

Abstract: The objective of the present paper is to develop a methodology that could allow the representation of the analytical hyporheic flux equation model (AHF) in a numerical model done in MODFLOW. Therefore, the scope of the research is to show the viability of the methodology suggested in a real case (Biebrza river, Poland, Europe). Considering that the model requires extensive manipulation in the creation of the packages, a test phase through the seepage package of MODFLOW is carried out with the aim of representi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…1). Analysis of groundwater-surface water interactions at the river stretch examined in this study was described in detail in Diaz et al (2020).…”
Section: Hyporheic Water Exchange Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Analysis of groundwater-surface water interactions at the river stretch examined in this study was described in detail in Diaz et al (2020).…”
Section: Hyporheic Water Exchange Researchmentioning
confidence: 99%
“…Some studies also showed that the influence of other environmental factors affecting hydromorphology were likely to induce HWE changes, which likely results in changing environmental conditions within the BMI's habitat niche (Magliozzi et al, 2019). To understand the variability of groundwater-surface water interactions in the Upper Biebrza (Anibas et al, 2012;Diaz et al, 2020) and to fill knowledge gaps on the near-natural status of this river, we conducted interdisciplinary research to identify HWE, selected hydraulic parameters of the river and abundances and taxonomic compositions of BMI, and make an attempt to reveal the interconnections between these processes. We hypothesized that (1) the distribution and taxonomic diversity of bottom-dwelling macroinvertebrates present different patterns that correspond to variable in-space conditions of HWE, and (2) the directions of HWE in a low dynamic, temperate, perennial lowland river influence the spatial patterns and the composition of bottom-dwelling macroinvertebrates more than the other environmental variables, such as the ones resulting from the river's hydromorphology and hydraulics.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [31] employed this software for groundwater resource assessment in the Longxi area of Daqing City, conducting simulation and prediction of groundwater. Diaz et al [32] aimed to develop a methodology for representing the analytical hyporheic flux equation model (AHF) in a numerical model performed in MODFLOW. Ostad, H et al [33] investigated the effects of karst conduit patterns on spring hydrographs, finding that conduit configuration and density, along with recharge type, significantly influence hydrograph characteristics such as peak discharge and recession rates.…”
Section: Introductionmentioning
confidence: 99%
“…Fleckenstein et al ( 2010) presented a study on groundwater-surface water interaction [3], the studied area in European Geosciences Union (EGU) General assembly was held in Vienna, and the researchers adopted numerical models to discover hypotheses and to improve new concept of models of GW-SW interactions. 2014) presented a study on interaction of aquifer and river-canal network near well field [5]. Haridwar and Madlala (2015), evaluated the surface water and groundwater interaction in higher part of Berg River catchment, South Africa [6], the researcher adopted in his study several methods oncoming to locate surface water and groundwater (GW-SW) interactions to count and describe the goodness of water sources in a cracked crag aquifer scheme in higher part of water area of the Berg River.…”
Section: Introductionmentioning
confidence: 99%